2010
DOI: 10.1002/chem.201000453
|View full text |Cite
|
Sign up to set email alerts
|

Localized Deposition of Au Nanoparticles by Direct Electron Transfer through Cellobiose Dehydrogenase

Abstract: Cellobiose dehydrogenase (CDH) is a fascinating extracellular fungal enzyme that consists of two domains, one carrying a flavin adenine dinucleotide (FAD) and the other a cytochrome-type heme b group as cofactors. The two domains are interconnected by a linker and electrons can shuttle from the FAD to the heme group by intramolecular electron transfer. Electron transfer between CDH and an electrode can occur by direct electron transfer (DET) and by mediated electron transfer (MET). This characteristic makes CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Moreover, the related enzymes and endogenous electron mediators contributed to the changes of electron transfer reaction thermodynamics, especially for gold systems [194]. By means of enzyme electrochemical system, gold nanoparticles could be locally deposited on Pd substrates through direct and mediated electron transfer by cellobiose dehydrogenase that consisted of two electron transfer mediate domains [195].…”
Section: Goldmentioning
confidence: 99%
“…Moreover, the related enzymes and endogenous electron mediators contributed to the changes of electron transfer reaction thermodynamics, especially for gold systems [194]. By means of enzyme electrochemical system, gold nanoparticles could be locally deposited on Pd substrates through direct and mediated electron transfer by cellobiose dehydrogenase that consisted of two electron transfer mediate domains [195].…”
Section: Goldmentioning
confidence: 99%
“…Such progress has prompted this new review on the bioelectrochemistry of CDH. One should also note that CDH has been used to make gold nanoparticles (AuNPs) and with the use of scanning electrochemical microscopy it was possible also to localise such AuNPs on surfaces with the help of CDH [59]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, Willner and co‐workers have shown that GOx can pump electrons directly to a confined metal particle and charge it . We demonstrated that the enzyme CDH catalyses the reduction of AuCl 4 − by DET from lactose in the presence of a catalytic metal surface, such as Pd, or AuNPs.…”
Section: Resultsmentioning
confidence: 81%
“…In a previous work, we explored the localized deposition of gold on Pd by CDH through DET . The localized bio‐catalyzed deposition of AuNPs by scanning electrochemical microscopy (SECM) was observed at pH 5.…”
Section: Introductionmentioning
confidence: 99%